Biochanin A prevents 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin-induced adipocyte dysfunction in cultured 3T3-L1 cells. Issue 9 (29th July 2019) - Choi, Eun Mi; Suh, Kwang Sik; Park, So Young; Chin, Sang Ouk; Rhee, Sang Youl; Chon, Suk
Abstract: 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) is a persistent environmental pollutant. TCDD accumulates in the food chain, mainly in the fatty tissues of the human body where it causes various toxic effects. Biochanin A is a natural organic compound in the class of phytochemicals known as flavonoids. We investigated whether biochanin A suppresses TCDD-induced loss of adipogenic action using 3T3-L1 adipocytes as a cell culture model of wasting syndrome. In the present study, biochanin A suppressed TCDD-induced loss of lipid accumulation. Pretreating the cells with biochanin A increased the levels of the adipogenesis-associated factors peroxisome proliferator-activated receptor γ and adiponectin, which were inhibited by TCDD. TCDD decreased insulin-stimulated glucose uptake, which was effectively restored by pretreatment with biochanin A. Biochanin A also inhibited the TCDD-driven decrease in production of insulin receptor substrate-1 and glucose transporter 4. These results suggest a preventive effect of biochanin A against TCDD in the development of insulin resistance and diabetes. TCDD increased production of intracellular calcium ([Ca 2+ ]i ), prostaglandin E2, cytosolic phospholipase A2, and cyclooxygenase-1, while reducing the level of peroxisome proliferator-activated receptor gamma coactivator 1-alpha. However, biochanin A inhibited these TCDD-induced effects. We conclude that biochanin A is an attractive compound for preventing TCDD-induced wasting syndrome.